How's life? 2013 Measuring well-being (Paris, 2013)
"Every person aspires to a good life. But what does "a good or a better life" mean? The second edition of How’s Life? provides an update on the most important aspects that shape people’s lives and well-being: income, jobs, housing, health, work-life balance, education, social connections, civic engagement and governance, environment, personal security and subjective well-being. It paints a comprehensive picture of well-being in OECD countries and other major economies, by looking at people’s material living conditions and quality of life across the population. Through a wide range of comparable well-being indicators, the report shows that countries perform differently in the various dimensions of well-being. For instance, low-income countries in the OECD area tend to do very well in subjective well-being and work-life balance, while their level of material well-being is much lower than that of other OECD countries. The report responds to the needs of citizens for better information on well-being and the needs of policy makers to give a more accurate picture of societal progress.